(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Artificial water bodies, including canals and reservoirs, play a significant role in human water management and agriculture. However, their presence also influences local microclimates and ecological systems. This article examines how these man-made aquatic systems affect temperature, humidity, air quality, and biodiversity in surrounding areas. The environmental benefits and challenges posed by artificial water bodies are discussed, along with sustainable management practices to mitigate negative impacts.